Manajemen Risiko Berbasis Syariah - Trimulato, Trimulato (Universitas Muhammadiyah Prof. DR. HAMKA, 2017)
This paper is descriptive qualitative, which describes risk management, and risk management in Islam, and risk management in shariah banking. The results of this paper indicate that risk management has a variety of processes, namely, the identification, evaluation and measurement, and management of risk. Risk management has been in line with Islam and different maysir. As well as risk management in Islamic banks have been set by the Indonesian bank in order to maintain the existence and improve the quality of shariah banking.